Improvement of Plasmid Volumetric Yield by Addition of Glycerol and Phosphate Buffer in Escherichia coli TOP10 Batch Culture - Anindyajati; Afifah, Salma Aulia; Riani, Catur; Tan, Marselina Irasonia; Natalia, Dessy; Giri-Rachman, Ernawati Arifin; Artarini, Anita (Bogor Agricultural University, Indonesia, 2024)
The investigation of mRNA development has gained substantial interest, particularly in the ex vivo and in vivo therapy. mRNA is widely used for the development of gene editing-based therapies and mRNA vaccines. The aim of this study was to optimize the medium and harvest time to increase plasmid DNA production as part of mRNA production. This study modified used a medium modification approach to achieve high density culture of Escherichia coli TOP10 pGEMT-N in batch cultivation method. Various media formulations were assessed, including LB; LB with phosphate buffer (K2HPO4 12.549 g/L and KH2PO4 2.31 g/L); LB with glycerol (50 g/L); LB with glycerol and phosphate buffer; LB with phosphate buffer, glycerol, glucose (15 g/L), and galactose (15 g/L). The effect of additional carbon sources and phosphate buffer on culture density was measured through OD600 and wet cell weight analysis. The highest OD600 and wet cell weight was observed when LB with glycerol and phosphate buffer was used, with OD600 of 4.78±0.14 and wet cell weight of 36.00±0.63 mg/ml. Plasmid DNA was subsequently isolated from these cultures following 5- and 7.5-hour incubation periods. The utilization of LB medium with glycerol and phosphate buffer resulted in a substantial increase in the volumetric concentration of plasmid DNA of 1,516.97±385.00 ng/ml after 5 hours of incubation. In conclusion, a remarkable enhancement in plasmid DNA volumetric yield within 5 hours was achieved by addition of glycerol and phosphate buffer to LB medium, leading to incubation period.